2013
DOI: 10.3201/eid1903.121156
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio choleraeNon-O1, Non-O139 Serogroups and Cholera-like Diarrhea, Kolkata, India

Abstract: We identified 281 Vibrio cholerae non-O1, non-O139 strains from patients with diarrhea in Kolkata, India. Cholera-like diarrhea was the major symptom (66.0%); some patients (20.3%) had severe dehydration. These strains lacked the ctxA gene but many had hlyA, rtxA, and rtxC genes. Pulsed-field gel electrophoresis showed no genetic link among strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
72
2
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 11 publications
4
72
2
9
Order By: Relevance
“…Similarly, Vibrio incidence rates of 2-4% have also been reported from surroundings of Himachal Pradesh [31][32][33]. In comparison to our observation, higher Vibrio infection rates ranging from 10% to 15% are reported from different parts of India [34,35]. Furthermore, surveillance studies from Bangladesh reported up to 18% of Vibrio infections among diarrheal populations [3,37].…”
Section: Discussioncontrasting
confidence: 49%
“…Similarly, Vibrio incidence rates of 2-4% have also been reported from surroundings of Himachal Pradesh [31][32][33]. In comparison to our observation, higher Vibrio infection rates ranging from 10% to 15% are reported from different parts of India [34,35]. Furthermore, surveillance studies from Bangladesh reported up to 18% of Vibrio infections among diarrheal populations [3,37].…”
Section: Discussioncontrasting
confidence: 49%
“…С другой стороны, причина может заключаться в настолько высокой степени из-менчивости локуса ДНК, ответственного за синтез О-антигена, что за ней «не поспевает» никакое рас-ширение схем серотипирования. Действительно, если в 1930-е годы число известных серогрупп равнялось 7, то в 1970-х годах оно возросло до 60, в 1980-х -до 137, в 1990-х -до 193, а к началу текущего столетия их насчитывалось уже 206 [18,44] и, тем не менее, при использовании соответствующего набора типи-рующих сывороток часть штаммов по-прежнему не агглютинируется ни одной из них [18,25,58]. Еще сложнее обстоит дело в России: за неимением в рас-поряжении ни соответствующих мировым стандар-там наборов сывороток, ни типовых штаммов для их получения (кроме О2-О11, О13-О22, О24, О25, О27-О39) отечественными исследователями (сотрудника-ми РосНИПЧИ «Микроб», а затем и РостНИПЧИ) была разработана собственная схема серотипирова-ния [1], позволяющая идентифицировать 80 серо-групп НАГ-вибрионов, 45 из которых (О40-О84) не соответствуют описанным в мировой литературе, что делает невозможным сравнение полученных данных с данными зарубежных авторов.…”
Section: Problemy Osobo Opasnykh Infektsii [Problems Of Particularly unclassified
“…Во многих работах отмечено нарастание числа резистентных и полирезистентных штаммов с течением времени. Например, если сре-ди штаммов, выделенных от больных в Калькутте в 1989-1991 гг., ни один не обладал устойчивостью к налидиксовой кислоте [44], то среди выделенных там же с 2002 по 2010 год резистентных к этому ан-тибиотику было 57,6 % [25]. Приобретение как от-дельных, так и множественных маркеров резистент-ности в течение нескольких лет констатировано ря-дом авторов при изучении клинических штаммов из Индии [17], Таиланда [23], Индонезии [55].…”
Section: Problemy Osobo Opasnykh Infektsii [Problems Of Particularly unclassified
See 2 more Smart Citations